The correlation between multiple variable factors and the autocatalytic properties of cerium oxide nanoparticles based on cell viability. (21st May 2018) - Li, Changyan; Shi, Xiangcheng; Bao, Liang; Yang, Jingjie; Damirin, Alatangaole; Zhang, Jun
Abstract : A new strategy was developed for evaluating the autocatalytic property of Ce NPs under optimized reaction conditions by the PLSR method. Abstract : CeO2 nanoparticles (Ce NPs) have received considerable interest due to their unique autocatalytic property. In this paper, the autocatalytic properties of Ce NPs of three different sizes were measured in vitro using a human gastric cancer cell line (BGC-803) at different concentrations ranging from 20 ng μL −1 to 200 ng μL −1 . The evaluation model of the autocatalytic properties of the Ce NPs was built by partial least squares regression (PLSR) based on the Matlab software. Multiple variable factors were quantitatively analyzed in terms of regression and correlation. The model indicated that the concentration was the primary factor, followed by the size of the Ce NPs. The autocatalytic properties of the Ce NPs was also promoted by the specific surface area, the valence states of Ce, and the surface charge in the cell culture medium. This study attempted to establish a quantitative framework and supply a new strategy for evaluating the autocatalytic property of cerium oxide nanoparticles for their use in biological and medical fields.